Flexible circuit fine wire silver paste and preparation method thereof
By cross-linking reaction of polyurethane-modified flexible epoxy resin and saturated polyester resin, combined with polyvinyl butyral thickening resin and thixotropic agent, fine wire silver paste with a fineness less than 5 μm is prepared, which solves the problem of the difficulty of the prior art to meet the fine wire printing and high-density printing in the automotive electronics field, and achieves efficient fine wire silver paste preparation.
Patent Information
- Application Number
- CN202411577032.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The prior art is difficult to meet the printing requirements of silver paste fine wire in the automotive electronics field of 0.05 to 0.12mm and diffusion of 0.01 to 0.02mm, and at the same time it cannot meet the printing requirements of high-density fine wire.
Polyurethane modified flexible epoxy resin was cross-linked with saturated polyester resin solution, combined with polyvinyl butyral thickening resin and thixotropic agent, and through efficient stirring and grinding technology, fine silver paste with a silver content of 43 to 51% with a fineness less than 5μm was prepared.
The high-density fine-line printing of silver paste is realized, meeting the fine-line printing requirements in the automotive electronics field, and improving the bending, moisture and heat resistance of silver paste.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic components, and in particular relates to a flexible circuit fine line silver paste and a preparation method thereof. Background Art
[0002] PCB (Printed Circuit Board) is a carrier for the electrical connection of electronic components and is one of the important components of the electronics industry. With the requirements for miniaturization and arraying of electronic components, the density of circuit boards is also increasing to meet the demand. HDI-PCB (High Density Circuit Board) has higher line density per unit area, finer lines and spaces, and higher pad connection density. It is widely used in mobile phones, touch screen devices, laptops, digital cameras, 4G network communications, medical equipment, and various electronic parts in aircraft and automobiles. It can also be used to reduce the weight and overall size of products, as well as enhance the electrical performance of equipment.
[0003] Chinese patent CN108770194B discloses a method for preparing a conductive silver paste for printed circuits, which comprises the following steps: (1) preparing the required raw materials according to the weight ratio, 10 to 15 parts of spherical silver powder, 20 to 30 parts of flaky silver powder, 7 to 10 parts of graphene, 8 to 12 parts of epoxy-modified polyester resin, 10 to 15 parts of organic solvent, aluminum nitride, defoaming agent, and leveling agent; (2) preparing an organic carrier, and (3) preparing a conductive silver paste. The silver content of the conductive silver paste for printed circuits is relatively high. Although the line width meets the requirements of fine line printing of 0.05 to 0.12 mm, it cannot meet the requirements of printing within a diffusion range of 0.01 to 0.02 mm, and the thixotropy and conductivity cannot meet the requirements of high-density fine line printing.
[0004] Chinese patent CN105070349A discloses a conductive fine-line printing silver paste for capacitive touch screens and a preparation and use method thereof. The raw materials of the conductive fine-line printing silver paste for capacitive touch screens include the following components in weight proportions: 60 to 80 parts of silver powder, 6 to 10 parts of vinyl resin, 22 to 25 parts of solvent, 0.5 to 3 parts of color powder, and 1 to 5 parts of additives. The silver content of the conductive fine-line printing silver paste for capacitive touch screens is relatively high, and the line width can neither meet the printing requirements within 0.05 to 0.12 mm and the diffusion within 0.01 to 0.02 mm, nor meet the requirements of high-density fine line printing. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing a flexible circuit fine line silver paste. The flexible circuit fine line silver paste prepared by the method can meet the printing requirements of silver paste fine lines within 0.05 to 0.12 mm and diffusion within 0.01 to 0.02 mm in the automotive electronics field, and can also meet the requirements of high-density fine line printing.
[0006] A second object of the present invention is to provide a flexible circuit fine line silver paste.
[0007] In order to achieve one of the above purposes, the present invention adopts the following technical solution:
[0008] A method for preparing a flexible circuit fine line silver paste, the preparation method comprising the following steps:
[0009] Step S1, dissolving a saturated polyester resin in a first solvent to obtain a saturated polyester resin solution with a mass concentration of 35-45%; dissolving a polyvinyl butyral thickening resin in the first solvent to obtain a polyvinyl butyral thickening resin solution with a mass concentration of 15-25%;
[0010] Step S2, mixing the polyurethane modified flexible epoxy resin, the saturated polyester resin solution, the polyvinyl butyral thickening resin solution, the thixotropic agent, the isocyanate curing agent and the first solvent, heating to 60-80° C., and then stirring and dispersing at a stirring rate of 600-1200 rpm for 20-40 minutes to obtain an organic carrier;
[0011] In the step S2, the mass ratio of the polyurethane modified flexible epoxy resin, the saturated polyester resin solution, the polyvinyl butyral thickening resin solution, the thixotropic agent, the isocyanate curing agent and the first solvent is 8-15: 5-30: 10-20: 1-6: 1-4: 30-55;
[0012] Step S3, after adding the second solvent and the coupling agent into the container, stirring and dispersing them at a speed of 400 to 800 rpm for 10 to 20 minutes, then adding the mixture of silver powder and nano zirconium oxide powder, stirring and dispersing them at a speed of 1000 to 1200 rpm at a water bath temperature of 80 to 85° C. for 1 to 2 hours, then sealing, placing it on a rod mill for grinding for 20 to 28 hours, adding it into the organic carrier, and dispersing it at a speed of 800 to 1600 rpm for 50 to 70 minutes to form a coarse slurry;
[0013] In the step S3, the mass ratio of the silver powder, the nano zirconium oxide powder and the organic carrier is 43-51:1-3:47-55;
[0014] The mass of the second solvent is 0.15 to 0.25 times the sum of the mass of the silver powder and the zirconium oxide powder;
[0015] The mass of the coupling agent is 0.01 to 0.03 times the sum of the mass of the silver powder and the zirconium oxide powder;
[0016] In the step S3, the silver powder includes flaky silver powder and nano-scale silver powder;
[0017] Step S4: Grind the coarse slurry several times using a three-roll grinder, and then perform vacuum degassing under stirring at a rotation speed of 400 to 600 rpm to obtain a fine line silver paste with a fineness of less than 5 μm.
[0018] Further, in the step S1, the saturated polyester resin is one or more of ES100, ES110, ES120, ES160, ES210, ES215, ES240, ES300, ES320, ES350, ES360, ES410, ES420, ES450, ES500, ES510, and ES850;
[0019] The polyvinyl butyral thickening resin is any one of B-76, B-08HX, B-14HX, SD-5 and SD-6.
[0020] Furthermore, in the step S1 and the step S2, the first solvent is one or more of high boiling point complex ester DBE, mixed dibasic acid dimethyl ester, EGDA, diethyl succinate, dimethyl adipate, diethyl adipate, and isophorone;
[0021] In step S3, the second solvent is one or more of methyl formate, ethyl formate, propyl formate, isopropyl formate, butyl formate, isobutyl formate, isoamyl formate, benzyl formate, methyl acetate, sec-butyl acetate, EEP, PGDA, PGA, YDBE, propylene glycol methyl ether acetate, propylene glycol methyl ether, propylene glycol butyl ether, ethylene glycol butyl ether, and ethylene glycol ethyl ether.
[0022] Further, in the step S2, the polyurethane modified flexible epoxy resin is one or more of DER791, EPU-105, EPU-133L, EPU-300S, ERS-005, NPER-133L, SL3411, SL3412, and SL3413;
[0023] The thixotropic agent is one of 6900-20X, AKN-7010, BYK-410, Anjeka4410, and Rheotech 2800.
[0024] Furthermore, in the step S3, the mass ratio of the flaky silver powder to the nano-scale silver powder in the silver powder is 90-99:1-10.
[0025] Furthermore, in the step S3, the mass ratio of the flaky silver powder to the nano-scale silver powder in the silver powder is 93-97:3-7.
[0026] Furthermore, in step S3, the average particle size of the flaky silver powder is 1.2 to 1.5 μm, and the specific surface area is 1.2 to 1.8 cm 2 / g, D100<5μm;
[0027] The average particle size of the nano-scale silver powder is 100-200 nm, and the specific surface area is 6.0-8.0 cm 2 / g.
[0028] Further, in step S3, the coupling agent is one or more of ZJ-316, ZJ-201, KR-38S, CT-114, NDZ-204, and LD-1070A;
[0029] Furthermore, in the step S4, the vacuum degree of the vacuum degassing is 0.6-0.8 MPa, the temperature is 20-30° C., the time is 40-50 minutes, and the number of grinding times is 6-10 times.
[0030] In order to achieve the second objective above, the present invention adopts the following technical solution:
[0031] A flexible circuit fine line silver paste is prepared by the above-mentioned preparation method.
[0032] Furthermore, the thixotropic index of the flexible circuit fine line silver paste is greater than 4, the silver content is 43-51%, the square resistance is 14.6-15.6 mΩ / □, the adhesion is 5B, the hardness is 5H, and the viscosity is 60-80 Pa·s.
[0033] In summary, the solution proposed by the present invention has the following technical effects:
[0034] The invention uses polyurethane modified flexible epoxy resin and saturated polyester resin solution to react with isocyanate curing agent with low deblocking temperature at low temperature (60-80 DEG C) to form a network structure, thereby improving the bending, moisture and heat resistance and chemical corrosion resistance of the silver paste, and achieving an adhesion of 5B with the ITO film; the organic bonding phase formed by the saturated polyester resin solution further improves the bending and thixotropy of the silver paste after low-temperature curing; the polyvinyl butyral thickening resin solution and the thixotropic agent are used to improve the viscosity and thixotropy of the silver paste when the silver content in the silver paste is low; and the flaky silver powder, the nano-scale silver powder and the control of the added amount are used to improve the viscosity and thixotropy of the silver paste under the premise of ensuring that the square resistance of the silver paste is not affected. , and at the same time improves the printing air permeability of the silver paste; the hardness of the silver paste is improved by the nano zirconium oxide powder, and the fineness of the silver paste is controlled; the fine-line conductive silver paste for flexible circuits of the present invention has a silver content of 43-51%, is cured at a low temperature of 110°C, has an adhesion to the ITO film of 5B, a hardness of 5H, a viscosity of 60-80Pa·s, and a thixotropic index of >4 (5rpm / 50rpm), which not only meets the printing requirements of silver paste fine lines within 0.05-0.12mm and diffusion within 0.01-0.02mm in the automotive electronics field, but also meets the requirements of high-density fine line printing; the fine-line conductive silver paste for flexible circuits of the present invention is applied to the HDI-PCB field, which is of great significance to expanding the application field of flexible circuit silver paste. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] Step S1, dissolving ES100 in DBE to obtain an ES100 solution with a mass concentration of 40%; dissolving B-76 in DBE to obtain a B-76 solution with a mass concentration of 20%;
[0038] Step S2, after mixing DER791, ES100 solution, B-76 solution, 6900-20X thixotropic agent, isocyanate curing agent and DBE, heating to 70° C., and then stirring and dispersing at a stirring rate of 1200 rpm for 40 minutes to obtain an organic carrier;
[0039] Among them, the mass ratio of DER791, ES100 solution, B-76 solution, 6900-20X thixotropic agent, isocyanate curing agent and DBE is 15:30:20:6:4:55;
[0040] Step S3, after adding methyl formate and ZJ-316 coupling agent into the container, stirring and dispersing at a speed of 600 rpm for 15 minutes, then adding the mixture of silver powder and nano zirconium oxide powder, stirring and dispersing at a water bath temperature of 82° C. at a speed of 1100 rpm for 1.5 hours, then sealing, placing on a rod mill for grinding for 24 hours, adding to the organic carrier, and dispersing at a speed of 1200 rpm for 60 minutes to form a coarse slurry;
[0041] The mass ratio of silver powder, nano zirconium oxide powder and organic carrier is 51:2:47. The mass of methyl formate is 0.25 times the mass of silver powder and zirconium oxide powder. The mass of ZJ-316 coupling agent is 0.03 times the mass of silver powder and zirconium oxide powder. Silver powder includes flaky silver powder and nano silver powder. The mass ratio of flaky silver powder and nano silver powder is 99:1. The average particle size of flaky silver powder is 1.2μm and the specific surface area is 1.2cm 2 / g, D100 is 3.5μm, the average particle size of nano-silver powder is 100nm, and the specific surface area is 6.0cm 2 / g.
[0042] Step S4: Grind the coarse slurry 10 times using a three-roll grinder, and then perform vacuum degassing under stirring at a rotation speed of 500 rpm to obtain a fine line silver paste with a fineness of 3.5 μm.
[0043] The vacuum degree of vacuum degassing is 0.6 MPa, the temperature is 20° C., and the time is 40 minutes.
[0044] Embodiment 2:
[0045] Step S1, dissolving ES110 in EGDA to obtain an ES110 solution with a mass concentration of 45%; dissolving B-08HX in EGDA to obtain a B-08HX solution with a mass concentration of 25%;
[0046] Step S2, after mixing EPU-105, ES110 solution, B-08HX solution, AKN-7010 thixotropic agent, isocyanate curing agent and EGDA, heating to 80° C., and then stirring and dispersing at a stirring rate of 900 rpm for 30 minutes to obtain an organic carrier;
[0047] Among them, the mass ratio of EPU-105, ES110 solution, B-08HX solution, AKN-7010 thixotropic agent, isocyanate curing agent and EGDA is 12:20:15:3:2:40;
[0048] Step S3, after adding the second solvent ethyl formate and the ZJ-201 coupling agent into the container, stirring and dispersing them at a speed of 800 rpm for 20 minutes, then adding the mixture of silver powder and nano zirconium oxide powder, stirring and dispersing them at a speed of 1200 rpm for 2 hours at a water bath temperature of 85° C., then sealing, placing it on a rod mill for grinding for 28 hours, adding it into the organic carrier, and dispersing it at a speed of 1600 rpm for 70 minutes to form a coarse slurry;
[0049] The mass ratio of silver powder, nano zirconium oxide powder and organic carrier is 47:1:52. The mass of methyl formate is 0.20 times the mass of silver powder and zirconium oxide powder. The mass of coupling agent ZJ-201 is 0.02 times the mass of silver powder and zirconium oxide powder. Silver powder includes flaky silver powder and nano silver powder. The mass ratio of flaky silver powder and nano silver powder is 95:5. The average particle size of flaky silver powder is 1.3μm and the specific surface area is 1.5cm 2 / g, D100 is 4.0μm, the average particle size of nano-silver powder is 150nm, and the specific surface area is 7.0cm 2 / g.
[0050] Step S4: Grind the coarse slurry 8 times using a three-roll grinder, and then perform vacuum degassing under stirring at a rotation speed of 600 rpm to obtain a fine line silver paste with a fineness of 4.0 μm.
[0051] The vacuum degree of vacuum degassing is 0.7 MPa, the temperature is 25° C., and the time is 45 minutes.
[0052] Embodiment 3:
[0053] Step S1, dissolving ES120 in isophorone to obtain an ES120 solution with a mass concentration of 35%; dissolving B-14HX in isophorone to obtain a B-14HX solution with a mass concentration of 15%;
[0054] Step S2, after mixing EPU-133L, ES120 solution, B-14HX, BYK-410 thixotropic agent, isocyanate curing agent and isophorone, heating to 75° C., and then stirring and dispersing at a stirring rate of 600 rpm for 20 minutes to obtain an organic carrier;
[0055] Among them, the mass ratio of EPU-133L, ES120 solution, B-14HX solution, BYK-410 thixotropic agent, isocyanate curing agent and isophorone is 8:5:10:1:1:30;
[0056] Step S3, after adding propyl formate and KR-38S coupling agent into the container, stirring and dispersing at a speed of 400 rpm for 10 minutes, then adding the mixture of silver powder and nano zirconium oxide powder, stirring and dispersing at a water bath temperature of 80° C. at a speed of 1000 rpm for 1 hour, then sealing, placing on a rod mill for grinding for 20 hours, adding to the organic carrier, and dispersing at a speed of 800 rpm for 50 minutes to form a coarse slurry;
[0057] The mass ratio of silver powder, nano zirconium oxide powder and organic carrier is 43:2:55. The mass of methyl formate is 0.15 times the mass of silver powder and zirconium oxide powder. The mass of coupling agent KR-38S is 0.01 times the mass of silver powder and zirconium oxide powder. Silver powder includes flaky silver powder and nano-scale silver powder. The mass ratio of flaky silver powder and nano-scale silver powder is 90:10. The average particle size of flaky silver powder is 1.5μm and the specific surface area is 1.8cm 2 / g, D100 is 4.5μm, the average particle size of nano-silver powder is 200nm, and the specific surface area is 8.0cm 2 / g.
[0058] Step S4: Grind the coarse slurry six times using a three-roll grinder, and then perform vacuum degassing under stirring at a rotation speed of 400 rpm to obtain a fine line silver paste with a fineness of 4.5 μm.
[0059] The vacuum degree of vacuum degassing is 0.8 MPa, the temperature is 30° C., and the time is 50 minutes.
[0060] Table 1 Performance index values of fine line silver paste of Examples 1 to 3
[0061] Performance parameters Example 1 Example 2 Example 3 Silver content, % 51 47 43 Viscosity, Pa·s 76.8 68.0 67.2 Thixotropic index, 5 / 50 4.6 4.4 4.1 Square resistance, mΩ / □ 14.6 15.3 15.6 Flexural resistance, 10 10 10 Adhesion 5B 5B 5B hardness 5H 5H 5H 0.05mm printing width, mm 0.0582 0.0588 0.592
[0062] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing a flexible circuit fine line silver paste, characterized in that: The preparation method comprises the following steps: Step S1, dissolving a saturated polyester resin in a first solvent to obtain a saturated polyester resin solution with a mass concentration of 35-45%; dissolving a polyvinyl butyral thickening resin in the first solvent to obtain a polyvinyl butyral thickening resin solution with a mass concentration of 15-25%; Step S2, mixing the polyurethane modified flexible epoxy resin, the saturated polyester resin solution, the polyvinyl butyral thickening resin solution, the thixotropic agent, the isocyanate curing agent and the first solvent, heating to 60-80° C., and then stirring and dispersing at a stirring rate of 600-1200 rpm for 20-40 minutes to obtain an organic carrier; In the step S2, the mass ratio of the polyurethane modified flexible epoxy resin, the saturated polyester resin solution, the polyvinyl butyral thickening resin solution, the thixotropic agent, the isocyanate curing agent and the first solvent is 8-15: 5-30: 10-20: 1-6: 1-4: 30-55; Step S3, after adding the second solvent and the coupling agent into the container, stirring and dispersing them at a speed of 400 to 800 rpm for 10 to 20 minutes, then adding the mixture of silver powder and nano zirconium oxide powder, stirring and dispersing them at a speed of 1000 to 1200 rpm at a water bath temperature of 80 to 85° C. for 1 to 2 hours, then sealing, placing it on a rod mill for grinding for 20 to 28 hours, adding it into the organic carrier, and dispersing it at a speed of 800 to 1600 rpm for 50 to 70 minutes to form a coarse slurry; In the step S3, the mass ratio of the silver powder, the nano zirconium oxide powder and the organic carrier is 43-51:1-3:47-55; The mass of the second solvent is 0.15 to 0.25 times the sum of the mass of the silver powder and the zirconium oxide powder; The mass of the coupling agent is 0.01 to 0.03 times the sum of the mass of the silver powder and the zirconium oxide powder; In the step S3, the silver powder includes flaky silver powder and nano-scale silver powder; Step S4: Grind the coarse slurry several times using a three-roll grinder, and then perform vacuum degassing under stirring at a rotation speed of 400 to 600 rpm to obtain a fine line silver paste with a fineness of less than 5 μm.
2. The preparation method according to claim 1, characterized in that: In the step S1, the saturated polyester resin is one or more of ES100, ES110, ES120, ES160, ES210, ES215, ES240, ES300, ES320, ES350, ES360, ES410, ES420, ES450, ES500, ES510, and ES850; The polyvinyl butyral thickening resin is any one of B-76, B-08HX, B-14HX, SD-5, and SD-6; In the step S1 and step S2, the first solvent is one or more of high boiling point complex ester DBE, mixed dibasic acid dimethyl ester, EGDA, diethyl succinate, dimethyl adipate, diethyl adipate, and isophorone; In step S3, the second solvent is one or more of methyl formate, ethyl formate, propyl formate, isopropyl formate, butyl formate, isobutyl formate, isoamyl formate, benzyl formate, methyl acetate, sec-butyl acetate, EEP, PGDA, PGA, YDBE, propylene glycol methyl ether acetate, propylene glycol methyl ether, propylene glycol butyl ether, ethylene glycol butyl ether, and ethylene glycol ethyl ether.
3. The preparation method according to claim 2, characterized in that: In the step S2, the polyurethane modified flexible epoxy resin is one or more of DER791, EPU-105, EPU-133L, EPU-300S, ERS-005, NPER-133L, SL3411, SL3412, and SL3413; The thixotropic agent is one of 6900-20X, AKN-7010, BYK-410, Anjeka4410, and Rheotech 2800.
4. The preparation method according to claim 3, characterized in that: In the step S3, the mass ratio of the flaky silver powder to the nano-scale silver powder in the silver powder is 90-99:1-10.
5. The preparation method according to claim 4, characterized in that: In the step S3, the mass ratio of the flaky silver powder to the nano-scale silver powder in the silver powder is 93-97:3-7.
6. The preparation method according to claim 5, characterized in that: In step S3, the average particle size of the flaky silver powder is 1.2 to 1.5 μm, and the specific surface area is 1.2 to 1.8 cm 2 / g, D100<5μm; The average particle size of the nano-scale silver powder is 100-200 nm, and the specific surface area is 6.0-8.0 cm 2 / g.
7. The preparation method according to claim 6, characterized in that: In step S3, the coupling agent is one or more of ZJ-316, ZJ-201, KR-38S, CT-114, NDZ-204, and LD-1070A.
8. The preparation method according to claim 7, characterized in that: In the step S4, the vacuum degree of the vacuum degassing is 0.6-0.8 MPa, the temperature is 20-30° C., and the time is 40-50 minutes.
9. A flexible circuit fine line silver paste, characterized in that: The flexible circuit fine line silver paste is prepared by the preparation method described in any one of claims 1 to 8.
10. The flexible circuit fine line silver paste according to claim 9, characterized in that: The flexible circuit fine line silver paste has a thixotropic index of >4, a silver content of 43-51%, a square resistance of 14.6-15.6 mΩ / □, an adhesion of 5B, a hardness of 5H, and a viscosity of 60-80 Pa·s.
Citation Information
Patent Citations
Special conductive filament printing silver slurry for capacitive touch screen and preparation and application methods of special conductive filament printing silver slurry
CN105070349A
Preparation method of conductive silver paste for printed circuits
CN108770194B
Low temperature curing laser silver paste and preparation method thereof
CN104934098A
Heterojunction silver paste and preparation method thereof
CN117894522A
Low-temperature curing type conductive silver paste, preparation method and application thereof
CN117976288A